Recyclable phosphor sheet based on polyvinyl alcohol for LED lighting using remote phosphor technology. (23rd February 2019) - Hämmer, M.; Gassmann, A.; Reller, A.; von Seggern, H.; Gutfleisch, O.; Stauber, R.; Zimmermann, J.
ABSTRACT: Recyclable free-standing phosphor sheets were prepared using the commercial phosphor Y3 Al5 O12 :Ce 3+ embedded in the organic binder polyvinyl alcohol as an alternative to conventionally used silicone. Such sheets can be used in energy down converting remote phosphor white light emitting diodes showing comparable quality as state-of-the-art phosphor sheets. The sheets presented in this work can be recycled by dissolution in water at room temperature. Subsequently, the phosphor is reclaimed by sedimentation with recycling rates of 92 wt.-%. The phosphor powder does not suffer any losses in quality or functionality compared to the starting material due to the recycling process.